Aprendizagem significativa do conceito de intensidade óptica utilizando o fotômetro de Bunsen - Conceição, Paulo da (2021)
The present study refers to the realization of an educational product for the construction and application of an oil stain photometer, according to the experience of the German chemist Robert Bunsen (1811-1899). It was decided to organize a Didactic Sequence in which activities to resume theoretical content on Electromagnetic Waves - Light was contemplated until the construction and application of the Oil Stain Photometer. As a theoretical framework, David Ausubel's Theory of Meaningful Learning (1918-2008) is used. The didactic sequence was applied to students in the 2nd grade of high school at a public school in Foz do Iguaçu, in the western region of Paraná. The activities carried out took place remotely through Google meet and Google classroom since the face-to-face classes are suspended due to the Pandemic of the new coronavirus. During the application of the educational product, the participating students showed interest in the experiment and reported that they were different and innovative classes compared to traditional classes. Since the product is easy to apply and the low cost for the construction of the Oil Stain Photometer are characteristics that make it accessible, regardless of a specific Physics laboratory. From the study carried out, it is concluded that the proposed educational product is suitable to show and verify that from a known light source and its luminosity characteristics we can determine the characteristics of another light source and that its application is viable and can be used in a way to contribute to meaningful learning of the students.